Intracerebral hemorrhage associated with warfarin versus non-vitamin K antagonist oral anticoagulants in Asian patients. (March 2019) - Woo, Ho Geol; Chung, Inyoung; Gwak, Dong Seok; Kim, Baik Kyun; Kang, Ji Hoon; Kim, Beom Joon; Bae, Hee-Joon; Han, Moon-Ku
Highlights: We compared outcomes and radiologic findings between NICH and WICH in Asian patients. Hematoma expansion and concomitant IVH rates were higher in WICH than in NICH. Both variables were associated with 3-month mortality after confounder adjustment. Radiological findings and clinical outcome at 3 months are more favorable in NICH. Abstract: Non-valvular atrial fibrillation patients receiving non-vitamin K antagonist oral anticoagulants (NOACs) have half the incidence of intracerebral hemorrhage (ICH) compared to those receiving warfarin. However, the differences in outcomes of NOAC-associated ICH (NICH) and warfarin-associated ICH (WICH) remain controversial. In this study, we investigated the clinical outcome and radiologic findings of ICH in Asian patients receiving NOACs or warfarin. We retrospectively reviewed the medical records of 544 ICH patients admitted to our hospital from January 2013 through December 2017, and compared the baseline demographics, clinical characteristics, ICH-related radiologic findings, and clinical outcome between the WICH and NICH groups. WICH and NICH were diagnosed in 46 and 13 patients, respectively. Lesions were located more frequently in the supratentorial deep area (45.7% and 46.2%) than the lobar area (30.4% and 30.8%) or brainstem and cerebellum (23.9% and 23.1%) in the WICH and NICH groups, respectively. The hematoma expansion and concomitant intraventricular hemorrhage (IVH) rate was significantly higher in the WICH group than in the NICH group (58.7% versus 7.7%, P  = 0.001 and 50.0% versus 15.4%, P  = 0.030, respectively). Hematoma expansion (odds ratio [OR]: 50.546; 95% confidence interval [CI]: 2.763–924.748; P  = 0.008) and concomitant IVH (OR: 9.240; 95% CI: 1.450–58.892; P  = 0.019) were independently associated with mortality at three months, after adjustment for confounding variables. Our results indicate that the radiological findings and clinical outcome at three months in patients with ICH are more favorable in those receiving NOAC therapy than in those receiving warfarin treatment.